Studies of Translation Models 3 : An Interaction Model of the Translation Process - Bathgate, Ronald (Meta, 1985)
AbstractA graphical notation permitting a detailed description of the translation process is developed and used to describe a number of different translation situations. This notation, based on a recently published model of the translation process, lays particular emphasis on the interactive nature of the translation process, i.e. on the fact that a translator does not work in isolation but is a member of a team whose task is to produce an optimum translation by joint effort. A written notation equivalent to the graphical notation is also briefly introduced.